Projeto elétrico modular para construção de ônibus urbanos: estudo de caso - Roth, Alencar Silveira (2015)
The operation market of the leading manufacturers Brazilian bus companies, has the caracteristic to customize your product according to the needs of its customers. This practice ends up causing many problems in the production process of the company, among them, the diversity in the electrical system of the bus. To solve these drawbacks productive, companies are investing in new software technologies, project, and manufacturing processes. This work presents a new methodology for design, fabrication, and assembly process of the electricalsystem of their product line for urban buses using modular designs solutions, exploring the global characteristics of the electrical system, for obtain a suitable manufacturing process their production needs of large scale, without influencing individual characterization of the product of each client. The new manufacturing process of the product presents in its results, significant improvements in engineering projects, how precision and time of project, manufacturing cost reduction and ease of maintenance of electrical networks.